Biological rhythm of cell-mediated immunity in man. - Eskola, J (1976)
The biological rhythm of the spontaneous lymphocyte transformation and the lymphocyte response to phytohaemagglutinin (PHA), concanavalin A (Con A) and purified protein derivative of tuberculin (PPD) was studied in six healthy male volunteers. The count of peripheral blood lymphocytes was increasing from 08.00 until 02.00 hr. The level of plasma cortisol was highest at 08.00 hr and lowest at 20.00 hr.The spontaneous lymphocyte transformation showed a biphasic cycle during the day; the peak values were observed at 08.00 and 20.00 hr and a significant depression was found at 14.00 hr. The response of peripheral blood lymphocytes to PHA and Con A varied inversely with the level of plasma cortisol. The PPD response was lowest at 08.00 hr, but the highest value was observed at 02.00 hr. No significant day to day variation was found in any of the parameters studied.